2015
DOI: 10.1128/jb.02542-14
|View full text |Cite
|
Sign up to set email alerts
|

devIIs an Evolutionarily Young Negative Regulator of Myxococcus xanthus Development

Abstract: During starvation-induced development of Myxococcus xanthus, thousands of rod-shaped cells form mounds in which they differentiate into spores. The dev locus includes eight genes followed by clustered regularly interspaced short palindromic repeats (CRISPRs), comprising a CRISPR-Cas system (Cas stands for CRISPR associated) typically involved in RNA interference. Mutations in devS or devR of a lab reference strain permit mound formation but impair sporulation. We report that natural isolates of M. xanthus capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
82
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 76 publications
4
82
1
Order By: Relevance
“…Another open question from the previous study is the role of DevT during development (10). The developmental defect of a devT mutant was more severe than those of devR and devS mutants, and the devT defect was not overcome by deletion of the dev promoter or devI.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Another open question from the previous study is the role of DevT during development (10). The developmental defect of a devT mutant was more severe than those of devR and devS mutants, and the devT defect was not overcome by deletion of the dev promoter or devI.…”
mentioning
confidence: 99%
“…Since the dev operon is a direct target of transcriptional activation by MrpC and FruA (9), a simple model proposes that dev expression governs commitment to sporulation (5). However, recent work showed that deletion of the dev promoter or the first gene of the operon, devI, suppresses the sporulation defects of devR and devS mutants (10). Since devR and devS mutants accumulate more dev transcripts than the wild type, it was proposed that overexpression of devI in the mutants inhibits sporulation.…”
mentioning
confidence: 99%
See 3 more Smart Citations